The Effect of Self Efficacy and Social Support on Intention of Entrepreneurship in The Era of Industrial Revolution 4.0 - Pasca Dwi Putra; Yesika Duma; Andri Zainal (Program Studi Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan Universitas Lambung Mangkurat, Banjarmasin, 2021)
The problem in this research is that the intention of student entrepreneurship is still low, it is evident that not all students are ready for entrepreneurship. This research was conducted at the Faculty of Economics, State University of Medan with a population of 89 students of Business Education. The sampling technique in this study used the Total Sampling method. Data collection techniques used were observation and questionnaires (questionnaires) whose measurements used a Likert scale and were processed statistically using the Correlation Coefficient test to test hypotheses one and two and with the Linear Regression Analysis test. The results of data analysis, it is obtained that the contribution of the independent variable to the dependent variable is known by the coefficient of determination (Adjusted R Square) which is classified as low which means the variables Self Efficacy and Social Support contribute to the effect on Entrepreneurial Intention. There is a positive and significant relationship between the effect of Self Efficacy and Social Support on the intention of entrepreneurship in the era of the Industrial Revolution 4.0 on Business Education students.